The culture of AIDS in Africa : hope and healing in music and the arts - Barz, Gregory F., 1960-; Cohen, Judah M. (Oxford University Press, 2011)
This title enters into the many worlds of expression brought forth across Africa by the ravaging presence of HIV/AIDS. Africans and non-Africans, physicians and social scientists, journalists and documentarians share here a common and essential interest in understanding creative expression in crushing and uncertain times. Chapters investigate and engage the social networks, power relationships, and cultural structures that enable the arts to convey messages of hope and healing, and of knowledge and good counsel to the wider community.